Entropy and expertise: assessing changes in pathologists' language over time using the UK Liver Pathology External Quality Assessment scheme - Jonathan P Callaghan; Katrina Z Freimane; Rachel M Brown; Alyn L Cratchley; Timothy J Kendall (The Journal of Pathology: Clinical Research)
Abstract External Quality Assessment (EQA) schemes are an important quality assurance tool and aim to ensure consistency among histopathologists. In this study, we use Shannon entropy as a novel metric to evaluate linguistic variability in the UK Liver Pathology EQA scheme. Analysing free‐text responses by participants over a decade, we aimed to quantify language trends in morphological assessments and clinicopathological diagnoses. Accounting for an increasing word count and when pathologists joined the scheme, our findings reveal a significant increase in entropy of morphological assessments over time, indicating growing linguistic diversity that may reflect the increasing complexity of liver pathology. Entropy of clinicopathological diagnoses over the same period did not provide clear evidence for convergent diagnostic language. High entropy corresponded to cases that elicited more diverse responses and could be considered more challenging, highlighting the utility of this method to identify potential areas for targeted education. We demonstrate entropy as a novel tool to analyse pathologist language and enhance quality assurance in the evolving pathology landscape.